Development of Chicken Egg Incubator Prototype with Blynk Notification - Hashim, Yasmin; Azmanirah Ab Rahman,; Munirah Ahmad Azraai, (Research and Innovation in Technical and Vocational Education and Training, 2023)
Abstrak: The development of a chicken egg incubator prototype with Blynk application notification is to assist farmers in monitoring the hatching process with notifications to users. This research presents the design and development of a chicken egg incubator. The aim is to test the functionality of this system designed to monitor and control the temperature of chicken eggs in the incubator using the Blynk application. The methodology used to develop this prototype is an adaptation of the prototype model which has 5 phases which are the phase of requirements analysis, initial design, building the prototype, evaluation and maintenance. In this design, researchers use a temperature control system that controls the temperature of the incubator. The system consists of temperature sensors, heating and cooling elements and controllers. If the temperature of the incubator exceeds a certain value, the cooling unit will operate to reduce the temperature while if the temperature is below another value, the heating element will start to operate to increase the temperature. Furthermore, the researchers used a motion sensor to detect the movement of the eggs. If there is movement inside the incubator, the owner of the incubator will get a notification about the status of the egg on the user's phone. In this writing, it is more about recommendations, procedures and expected results from the construction of this project.